Essentializing the binary self: individualism and collectivism in cultural neuroscience - Martinez Mateo, Marina; Cabanis, Maurice; Stenmanns, Julian; Krach, Sören (Frontiers in Human Neuroscience, 2013)
Within the emerging field of Cultural Neurosciences (CN) one branch of research focuses on the neural underpinnings of "individualistic/Western" versus "collectivistic/Eastern" self-views. These studies uncritically adopt essentialist assumptions from classic cross-cultural research, mainly following the tradition of Markus & Kitayama (1991), into the domain of functional neuroimaging. In this comment we analyze recent publications and conference proceedings of the 18th Annual Meeting of the Organization for Human Brain Mapping (2012) and problematize the essentialist and simplistic understanding of "culture" in these studies. Further, we argue against the binary structure of the drawn "cultural" comparisons and their underlying Eurocentrism. Finally we scrutinize whether valuations within the constructed binarities bear the risk of constructing and reproducing a postcolonial, orientalist argumentation pattern.